Zero‐mass flux and Cattaneo–Christov heat flux through a Prandtl non‐Newtonian nanofluid in Darcy–Forchheimer porous space. Issue 1 (25th July 2020) - Reddy, M. G.; Vijayakumari, P.; Kumar, K. G.; Shehzad, S. A.
Abstract: The Darcy–Forchheimer Prandtl fluid flow due to moving sheet is described here. The familiar energy transfer model, namely, the Cattaneo–Christov model of heat transportation, is adopted under thermal radiation phenomenon. The Prandtl non‐Newtonian nanofluid is accounted as a functioning fluid. The functioning fluid flows in Darcy–Forchheimer porosity space. The boundary‐layer and similarity variables are executed to reframe the mathematical expressions into simplified and single independent variable. Numerical solutions of nonlinear dimensionless expressions are calculated. The variations of distinct constraints on important quantities are demonstrated through tabular and pictorial forms. It is visualized that the velocity of non‐Newtonian nanofluid is enhanced significantly by incrementing the elastic parameter. Improving the thermophoretic and Brownian movement parametric values leads to higher profile of Prandtl nanofluid temperature.